Дибинецька фаянсова фабрика графів Браницьких на Київщині в світлі даних першоджерел - Школьна, О.В. (Археологія і давня історія України, 2018)
Статтю присвячено упорядкуванню існуючих відомостей про конкурентну Києво-Межигірській фаянсовій фабриці Дибинецьку фаянсову фабрику
графів Браницьких на Київщині. Більшість матеріалів вводиться до наукового обігу вперше, що
дозволяє переглянути окремі розділи з історії розвитку українського фаянсу доби його «золотого періоду», цебто ХІХ ст. Article is devoted ordering of existing data about competitive Kyivo-Mezhigorskoj to faience factory to
Dibinetsky faience factory of counts Branitsky in an area of the Kyiv province. The majority of materials
is introduced in scientific use for the first time, that allows to reconsider separate sections from a history of
development of the Ukrainian faience of its time of «the gold period», namely 19th centuries. The list of products
amazes. Services from white faience of the first grade on 4 roubles, soup vases of «the English style» with
printing drawing on 7 roubles 10 copeck and 20 copeck painted on 9 roubles, flowerpots of a new style «Lily»
30 copeck painted on 4 rouble the Sculpture «the Young lion, the Lamb and the Dog» were the most expensive
things from this register «Goat» cost on 30 copeck for a piece in the sealed up kind, 40 in painted, no less than.
«Partridge» in last type of a decor — is almost twice more expensive, 75 copeck for a piece. Banks pharmaceutical
— from 5 copeck for a piece, pots on 10 copeck for a piece, smoking tubes-«stambulki» («Turkish woman») and a bowl for salad on 15 copeck for a piece were the cheapest among products of the first grade.